Effect of fat thickness and temperature on ADG and F/G ratio in finishing swine - David A Nichols; D R Ames; G L Allee; Robert H Hines (Kansas Agricultural Experiment Station Research Reports, 1978)
Fat and lean pigs were observed at temperatures of 0(32F), 5(41F), 10(50F), 15(59F), and 20C(68F). In comparing fat and lean pigs no significant differences were observed in feed-to-gain ratio or average daily gain. Pigs housed at 32 and 41F gained significantly slower and less efficiently than those housed at 50, 59, or 68F. No differences in performance were observed among the last three groups. Increased huddling, longer hair coats and increased shivering were observed at the lower temperatures.; Swine Day, Manhattan, KS, November 9, 1978
Keywords: Swine day; 1978; Kansas Agricultural Experiment Station contribution; no. 79-105-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 342; Swine; Fat thickness; Temperature; ADG; F/G ratio; Finishing pigs